Impact of admission and early persistent stress hyperglycaemia on clinical outcomes in acute pancreatitis - Yang, Xinmin; Shi, Na; Yao, Linbo; He, Wenhua; Zhu, Ping; Li, Sheyu; Li, Lan; Li, Yuying; Liu, Shiyu; Deng, Lihui; Jin, Tao; Liu, Tingting; et al. (Frontiers in Endocrinology, 2022)
Background: To determine the impact of glucose levels at admission and during first week (early phase) on clinical outcomes in patients with acute pancreatitis (AP) and to investigate the relationship between stress hyperglycaemia (SHG) and hypertriglyceridaemia (HTG). Methods: Two independent and prospective databases were retrospectively analysed (n = 1792). Patients admitted with pain of less than 48 hours and confirmed AP were included. SHG was defined as admission blood glucose ≥ 10.00 mmol/L (non-diabetic) or ≥ 16.67 mmol/L (diabetic). Blood glucose records for the first week were inspected to determine whether SHG lasted ≥ 48 hours (persistent) or < 48 hours (transient). Clinical outcomes were compared between designated patient groups using multivariate and trend analyses. The correlation between SHG and HTG (serum triglyceride ≥ 5.65 mmol/L) was also analysed. Results: On admission, SHG was present in 27.8% (499/1792) patients; during the first 48 hours of admission, transient and persistent SHG was found in 31% (556/1792) and 8.0% (144/1792) patients, respectively. Admission SHG was associated with higher incidence of persistent organ failure, acute necrotic collection, major infection, and mortality as well as prolonged length of hospital stay (all P < 0.05). Duration of SHG was also associated with worsened clinical outcomes (all P < 0.05). In HTG-AP patients, more severe clinical outcomes were observed in those who concomitantly had SHG (P < 0.05). Conclusions: Admission and persistent SHG during the first week of admission worsens clinical outcomes of AP patients. These effects are more pronounced when admission HTG co-existed.